CORRUPTION AND DECENTRALISATION: SOME EVIDENCE IN INDONESIA - Ferry Prasetyia (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
This paper seeks to disentangle the relationship between decentralisation andcorruption In Indonesia. The implementations of decentralisation in Indonesia in2001, on one hand give an opportunity for local government for more responsiveand accountable to citizens. Therefore, service delivery will improve and corruptionwill decline. On the other hand, more decentralisation has a positive impact oncorruption, raising individual propensity to accept bribes due to an increasing anopportunities for corruption at local level. Some studies show that the implementationof decentralisation in Indonesia tends to an increasing in corruption at local level.However, some local governments have an initiative to addressing the problem ofcorruption through several approaches.Keywords: Decentralisation, corruption, and local government.